ClassifySolve

ClassifySolve - y 3 2xy)dx(3x 4 y 2 – x 2)dy = 0(8(x 2 y 2 x dx xy dy = 0(9 x dy = y x 3 2x 2 2x dx(10 dy y cot x = 5 e cosx dx(11 y lny dx(x ln

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Classify and Solve First Order O.D.E. (1) x 2 (y + 1)dx + y 2 (x -1) dy = 0 (2) 4x dy - y dx = x 2 dy (3) x dy - y dx = x 2 ! y 2 dx = 0 (4) (1 + 2 e x y ) dx + 2 e x y (1 - x/y)dy = 0 (5) (x + y) dx + (3x + 3y - 4) dy = 0 (6) cot ø d ! + ! dø = 0 (7) (4x 3
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: y 3- 2xy)dx + (3x 4 y 2 – x 2 )dy = 0 (8) (x 2 + y 2 + x) dx + xy dy = 0 (9) x dy = y + x 3 + 2x 2- 2x dx (10) dy + y cot x = 5 e cosx dx (11) y lny dx + (x - ln y) dy = 0 (12) dy + 1/3 y = 1/3(1 - 2x)y 4 dx...
View Full Document

This note was uploaded on 07/23/2011 for the course MAP 2302 taught by Professor Staff during the Fall '08 term at FIU.

Ask a homework question - tutors are online